2023
DOI: 10.1177/07067437221150508
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, Acceptability, and Safety of Faecal Microbiota Transplantation in the Treatment of Major Depressive Disorder: A Pilot Randomized Controlled Trial

Abstract: Objectives Perturbations of the intestinal microbiota have been associated with mental health disorders, including major depressive disorder (MDD). Therefore, faecal microbiota transplantation (FMT) holds promise as a microbiota-modulating treatment for MDD. Yet, to date, there are no published controlled studies evaluating the use of FMT for MDD. This study aimed to address this gap by evaluating the feasibility, acceptability, and safety of FMT for MDD. Methods The study was an 8-week, double-blind, 2:1 para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 55 publications
(64 reference statements)
1
15
0
Order By: Relevance
“…Depression is a heterogeneous mood disorder with a complex yet not sufficiently understood neurobiology that has strong links to a dysfunction of the microbiome-gut-brain axis (Gheorghe et al, 2022). Clinical studies have found differences in the composition of the gut microbiota in patients with depression compared to individuals without mental disorders (Valles-Colomer et al, 2019;Socała et al, 2021;Green et al, 2023;Modesto Lowe et al, 2023). Common to all studies is an increase in the number of lactic acid-producing bacteria such as Lactobacillus, Streptococcus, and Enterococcus, and a decrease in the number of bacteria producing SCFAs (mainly butyrate) such as Faecalibacterium and Coprococcus (Table 4) (Valles-Colomer et al, 2019;McGuinness et al, 2022).…”
Section: Gut Microbiome and Depressionmentioning
confidence: 99%
See 3 more Smart Citations
“…Depression is a heterogeneous mood disorder with a complex yet not sufficiently understood neurobiology that has strong links to a dysfunction of the microbiome-gut-brain axis (Gheorghe et al, 2022). Clinical studies have found differences in the composition of the gut microbiota in patients with depression compared to individuals without mental disorders (Valles-Colomer et al, 2019;Socała et al, 2021;Green et al, 2023;Modesto Lowe et al, 2023). Common to all studies is an increase in the number of lactic acid-producing bacteria such as Lactobacillus, Streptococcus, and Enterococcus, and a decrease in the number of bacteria producing SCFAs (mainly butyrate) such as Faecalibacterium and Coprococcus (Table 4) (Valles-Colomer et al, 2019;McGuinness et al, 2022).…”
Section: Gut Microbiome and Depressionmentioning
confidence: 99%
“…There is evidence of a correlation between certain gut bacteria and depression symptoms (Simpson et al, 2021;McGuinness et al, 2022). However, their involvement in the pathophysiology of the mental disorder is not well understood (Green et al, 2023). Meta-analyses suggest that probiotics as an adjunctive treatment may reduce depressive symptoms, (Chao et al, 2020;El Dib et al, 2021;Green et al, 2023).…”
Section: Gut Microbiome and Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…A pilot double-blind randomised controlled study (RCT) in humans by Green et al (2023) demonstrated good feasibility, acceptability and safety of FMT enemas in the treatment of MDD. All feasibility targets were met or exceeded, and the findings are encouraging and support further research into FMT.…”
Section: Faecal Microbiota Transplantmentioning
confidence: 99%